Sex differences and the effect of female sex hormones on auditory function: a systematic review - Aloufi, Nada; Heinrich, Antje; Marshall, Kay; Kluk, Karolina (Frontiers in Human Neuroscience, 2023)
Aims First, to discuss sex differences in auditory function between women and men, and whether cyclic fluctuations in levels of female sex hormones (i.e., estradiol and progesterone) affect auditory function in pre-menopausal and post-menopausal women. Second, to systematically review the literature concerning the discussed patterns in order to give an overview of the methodologies used in research. Last, to identify the gap in knowledge and to make recommendations for future work. Methods for the systematic review Population, Exposure, Control, Outcome and Study design (PECOS) criteria were used in developing the review questions. The review protocol follows the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and was pre-registered in the Prospective Register of Systematic Reviews (PROSPERO; CRD42020201480). Data Sources: EMBASE, PubMed, MEDLINE (Ovid), PsycINFO, ComDisDome, CINAHL, Web of Science, Cochrane Central Register of Controlled Trials (CENTRAL) via Cochrane Library, and scanning reference lists of relevant studies, and internet resources (i.e., Mendeley) were used. Only studies published between 1999 and 2022, in English, or in English translation, were included. The quality of evidence was assessed using the Newcastle-Ottawa Scale (NOS). Results Sex differences: Women had more sensitive hearing (measured at the level of peripheral and central auditory system) than men. Cyclic fluctuations: Auditory function in women fluctuated during the menstrual cycle, while no such fluctuations in men over the same time period were reported. Hearing sensitivity improved in women during the late follicular phase, and decrease during the luteal phase, implying an effect of female sex hormones, although the specific effects of estradiol and progesterone fluctuations on the central auditory system remain unclear. Hearing sensitivity in women declined rapidly at the onset of menopause. Conclusion The review has shown the following. Consistent sex differences exist in auditory function across the auditory pathway with pre-menopausal women often showing better function than age-matched men. Moreover, pre-menopausal women show fluctuations in hearing function across the menstrual cycle with a better function during the peak of estradiol or when the ratio of estradiol to progesterone is high. Third, menopause marks the onset of hearing loss in women, characterized by a rapid decline in hearing sensitivity and a more pronounced loss than in age-matched men. Finally, the systematic review highlights the need for well-designed and -controlled studies to evaluate the influence of estradiol and progesterone on hearing by consistently including control groups (e.g., age-matched man), using objective tests to measure hormonal levels (e.g., in saliva or blood), and by testing participants at different points across the menstrual cycle. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42020201480, identifier CRD42020201480.